2003
DOI: 10.1080/0961452032000112383
|View full text |Cite
|
Sign up to set email alerts
|

Microfinance and social capital: Does social capital help create good practice?

Abstract: Microfinance and social capital: does social capital help create good practice? Sanae ItoThe role of organising and disseminating knowledge as a global public good has become a major preoccupation of international development organisations. One area in which they are particularly active is support for microfinance programmes in developing countries. More recently, the microfinance 'best practices' deposited in, and disseminated by, these international organisations have been associated with social capital. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 9 publications
2
42
0
Order By: Relevance
“…They operated under particular pressure to secure high rates of repayment as their institutions sought financial sustainability, and were assessed primarily on the basis of their credit-delivery performance. Findings in other countries have been similar (Ito, 2003;Rahman, 1999b;Reinke, 1998;Schreiner, 1999). Goetz concluded that the importance and influence of field workers was in principle reflected in whether and how they reconciled their organisations" goals with their own personal preferences.…”
Section: Fieldworkers: a Brief Reviewsupporting
confidence: 59%
See 4 more Smart Citations
“…They operated under particular pressure to secure high rates of repayment as their institutions sought financial sustainability, and were assessed primarily on the basis of their credit-delivery performance. Findings in other countries have been similar (Ito, 2003;Rahman, 1999b;Reinke, 1998;Schreiner, 1999). Goetz concluded that the importance and influence of field workers was in principle reflected in whether and how they reconciled their organisations" goals with their own personal preferences.…”
Section: Fieldworkers: a Brief Reviewsupporting
confidence: 59%
“…Goetz concluded that the importance and influence of field workers was in principle reflected in whether and how they reconciled their organisations" goals with their own personal preferences. Ito (2003) observed that field workers with diverse roles faced the rival demands between increasing loan disbursement and repayment as compared with borrowers" requirements to be sensitive to their own specific circumstances and requirements. Ahmad (2000Ahmad ( , 2002 also argued that the microfinance literature has evaluated the activities of Non-governmental organisations (NGOs) without sufficient reference to s:\staff\repositories\fulltext\business school\4288\journal article-acforum.doc 6 the views of those who actually work with clients.…”
Section: Fieldworkers: a Brief Reviewmentioning
confidence: 99%
See 3 more Smart Citations